Breadwinner role and economic decision-making: Experimental evidence from Kenya - Vitellozzi, Sveva; Savadori, Lucia; Davis, Kristin E.; Azzarri, Carlo; Kinuthia, Dickson; Ronzani, Piero (International Food Policy Research Institute, 2025)
In several countries and settings, especially in low- and middle-income countries, men are expected to act as primary economic providers for their households, bearing the psychological and social burdens associated with this role. Despite its potential consequences, the effects of the breadwinner role on economic decision-making are understudied, particularly among poor households. This study investigates how gendered breadwinner expectations shape economic behavior in rural Kenya. Using a lab-in-the-field experiment among 400 smallholder farmers in Vihiga County, we test how psychological and social pressures associated with being the breadwinner of the family influence decision-making in both individual work choices and collective decisions. Participants completed a real-effort task choosing either a high-effort, high-reward option or a low-effort, low-reward alternative, followed by a public goods game framed around communal seed bank contributions. Results reveal that the heightened strain of the main breadwinner led male participants to reduce contributions to the communal seed bank by 0.2 standard deviations, while it did not affect their productivity in the real-effort task. These behavioral shifts suggest that the psychological consequences of breadwinner strain can undermine cooperation and the adoption of sustainable agriculture practices. Addressing the pressures of breadwinning can foster both economic resilience and social cohesion.